Hit the Ground Running with Visual C++.Net - Amiram Neiman (Cengage Learning, Inc, 2006)
Providing easy-to-understand tutorials, this book will help programmers hit the ground running in their development efforts! Beginning and advanced programmers alike will quickly establish competency in the usage of the Visual C++.NET language through current best coding practices and a modular design that provides clear entry points for people of all abilities. Useful for programming projects that are both academic and industrial in nature, this book provides the information necessary to become productive in the .NET framework, and will have users deploying robust, highly secure applications in minimal time